SIKAP BAHASA MAHASISWA PPG PRAJABATAN BAHASA INDONESIA GELOMBANG 1 TAHUN 2023 UNIVERSITAS PASUNDAN - Fahman Nur Faizi (Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to analyze the language attitudes of Indonesian Language Pre-service Teacher Education (PPG) students, Batch 1, 2023, at Universitas Pasundan, towards the preservation of the Sundanese language. This research used a descriptive quantitative method, with data collected through questionnaires distributed to 20 students. Data were analyzed using descriptive statistics to depict students’ attitudes in three aspects of language attitudes: loyalty, pride, and awareness of language norms. The results showed that students' attitudes towards the Sundanese language were more positive in family and neighborhood contexts but declined in educational and technological contexts. In general, students displayed a positive attitude towards the Indonesian language and favored foreign languages in formal and digital communication. These findings indicate that efforts to preserve the Sundanese language require more attention in educational and technological realms to prevent it from being overshadowed by the dominance of national and international languages.